Extreme Climate Events and Energy Market Vulnerability: A Systematic Global Review - César Dubbier Castro Hernandez; Lina Montuori; Manuel Alcázar-Ortega; Piotr Olczak (Applied Sciences)
This research study deals with the analysis of climate catastrophes that have occurred worldwide and in what measure they have affected communities, in an economic and social point of view, and energy markets in general over time. A chronological sweep across Europe has been carried out in order to evaluate the different consequences that phenomena such as hurricanes, winter storms, and floods have had, especially on the energy prices. Moreover, the effects of the variability of renewable generation during climate disasters not only in Europe but also in North America, Australia, and Latin America have been discussed. Furthermore, best practices and novel strategies for climate adaptations have been identified in different countries, and the results show how energy planning integrated within a systematic diversification of energy sources and investment in infrastructure and advanced technologies such as distributed generation and digital twins can be crucial to enhance the reliability of energy systems.